Inoculação, manejo do nitrogênio e decomposição dos resíduos vegetais de cereais de inverno na produção de grãos e silagem de milho - Bertoncelli, Patricia (2014)
The quest for greater productivity and concern for sustainability, it makes the constant search for alternatives that obtain high productivity sustainably and nutrient cycling, biological nitrogen fixation and proper N fertilization some of these alternatives. In order to validate these alternatives aim with this work was to verify the influence of inoculation and nitrogen management in winter cereals, rates of decomposition of plant residues and its influence on the yield of grain and corn silage. The work consists of three chapters with the first entitled "effect of inoculation with Azospirillum brasilense and seed treatment in the initial development of four cultivars of wheat" which aims to assess the development and initial establishment of wheat cultivars subjected to treatment and inoculating seeds with Azospirillum brasilense bacteria. The second titled "inoculation, waste straw and nitrogen on grain yield and quality of corn silage " aims to evaluate the influence of applying Azospirillum brasilense associated with different levels of nitrogen on yield components and quality of silage corn in no-till crop residues on different system. The third "different decomposition of crop residues on different nitrogen rates and application Azospirillum brasilense" aims to obtain a characterization of the decomposition of the macronutrients of different crops / cultivars, under the influence of different nitrogen and inoculant application based Azospirillum. The different crop residues have different productivities as well as provide change in silage quality. The application of Azospirillum brasilense causes increase in corn yield, change in the initial development of wheat seedlings, as well as providing variation in the decomposition of plant residues. The use of seed treatment affects initial growth of wheat seedlings, however, they have a compensatory gain minimizing this effect.